2020
DOI: 10.1002/ecs2.3231
|View full text |Cite
|
Sign up to set email alerts
|

Reframing tropical savannization: linking changes in canopy structure to energy balance alterations that impact climate

Abstract: Tropical ecosystems are undergoing unprecedented rates of degradation from deforestation, fire, and drought disturbances. The collective effects of these disturbances threaten to shift large portions of tropical ecosystems such as Amazon forests into savanna‐like structure via tree loss, functional changes, and the emergence of fire (savannization). Changes from forest states to a more open savanna‐like structure can affect local microclimates, surface energy fluxes, and biosphere–atmosphere interactions. A pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 145 publications
0
35
0
Order By: Relevance
“…Continued monitoring of these plots in regular intervals (annual or biannual) is important to improve our understanding of the related carbon fluxes (emissions and uptake) [ 58 ], the recovery time to pre-fire states [ 20 ] and/or eventual disruption of carbon dynamics by tree mortality (e.g. caused by additional drought and fire events) [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continued monitoring of these plots in regular intervals (annual or biannual) is important to improve our understanding of the related carbon fluxes (emissions and uptake) [ 58 ], the recovery time to pre-fire states [ 20 ] and/or eventual disruption of carbon dynamics by tree mortality (e.g. caused by additional drought and fire events) [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have already shown the effects of these variables on post-fire tree mortality in tropical forests [ 21 , 22 ]; however, our results quantitatively characterize how trees with certain resilient plant traits (greater sizes and WD) still may not be able to survive under high-intensity fires. Since fire intensity is linked to drought severity [ 9 ], forest fire impact and extent in the less seasonal Amazon may increase in the future with widespread anthropogenic disturbances degrading forest canopies and creating hotter drier understorey conditions and with more widespread and intense droughts forecasted as a result of climate change [ 2 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terrestrial ecosystems, such shifts occur when the dominant vegetation type is replaced by a different functional type. Prominent examples include the conversion of tropical forests to savannahs and grasslands after being burned and cleared (Stark et al, 2020) and the invasion of grassland ecosystems by woody plants, creating a savannah ecosystem (Breshears, 2006). These changes imply altered ecosystem function and services (Folke et al, 2004), and if the new vegetation type is persistent, then it represents an alternative stable state (Suding et al, 2004).…”
Section: An Introduction To Vegetation‐type Conversion (Vtc)mentioning
confidence: 99%
“…The transition between humid tropical forest and savanna, one of the most striking ecotones on Earth, is currently subject to multiple drivers of change, including increased climate variability, rising atmospheric CO 2 and land‐use change (Aleman & Fayolle, 2020; Oliveras & Malhi, 2016 and references therein). Changes in this transition have important implications for land–atmosphere interactions through its effects on biogeochemical cycles, energy budget and hydrology (Bond, 2008; Stark et al., 2020). The existence of this transition has been attributed to multiple abiotic and biotic factors, such as the amount and seasonality of precipitation, fire regimes, herbivory pressure, soil properties, species adaptations and competitive strategies, and human pressure (Aleman et al., 2020; Bond, 2008; D’Onofrio et al., 2019; Hirota et al., 2011; Hoffmann et al., 2012; Langan et al., 2017; Murphy & Bowman, 2012; Oliveras & Malhi, 2016; Staal et al., 2016; Staver et al., 2011; Wuyts et al., 2017; Xu et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The existence of this transition has been attributed to multiple abiotic and biotic factors, such as the amount and seasonality of precipitation, fire regimes, herbivory pressure, soil properties, species adaptations and competitive strategies, and human pressure (Aleman et al., 2020; Bond, 2008; D’Onofrio et al., 2019; Hirota et al., 2011; Hoffmann et al., 2012; Langan et al., 2017; Murphy & Bowman, 2012; Oliveras & Malhi, 2016; Staal et al., 2016; Staver et al., 2011; Wuyts et al., 2017; Xu et al., 2018). There is typically an array of abiotic factors that determine where humid forest or savanna can exist, constrained mostly by water limitations and fire (Oliveras & Malhi, 2016; Scheffer et al., 2001; Stark et al., 2020). Forests predominate in conditions of high annual rainfall and a shorter dry season, whereas savannas prevail with lower annual rainfall, a longer dry season and frequent fire occurrence (Hirota et al., 2011; Staver et al., 2011).…”
Section: Introductionmentioning
confidence: 99%